Membangun Jiwa Wirausaha melalui Pengolahan Selai Pepaya Rasa Nanas di Kelompok Wanita Tani (KWT) Srikandi 02 Desa Apk Bandung Kecamatan Selupu Rejang - Rizky Septika Utami; Rini Suryani; Meko Gustian; Venti Novitas Sari; Darwan Effendi (Fakultas Teknik Universitas Cenderawasih, 2026)
Universities are educational institutions that have an important role in addressing various problems in rural areas by motivating, empowering, and broadening the perspectives of local communities. Through community service activities, universities can contribute to improving community skills and encouraging economic independence. This community service program aims to foster an entrepreneurial spirit among female farmers in APK Bandung Village, Selupu Rejang District, through training and assistance in producing pineapple-flavored papaya jam as a value-added agricultural product. The program was conducted in November 2025 and involved one partner, namely the Srikandi Women's Farmers Group (Kelompok Wanita Tani/KWT) 02 of APK Bandung Village. The implementation stages included socialization, product-making demonstrations, mentoring, monitoring, and evaluation activities. These stages were designed to enhance participants’ knowledge and practical skills in processing local agricultural commodities into marketable products. Out of 20 registered members of KWT Srikandi, 17 members attended and actively participated in the program. The results of the evaluation, based on questionnaires distributed to participants, showed that approximately 64.70% of the members demonstrated an entrepreneurial spirit. These findings indicate that the program contributed positively to increasing entrepreneurial awareness and encouraging the development of small-scale rural business opportunities among female farmers.